Motivational Interviewing As an Adjunct to Periodontal Therapy—A Systematic Review - Kopp, Svenja L.; Ramseier, Christoph A.; Ratka-Krüger, Petra; Woelber, Johan P. (Frontiers in Psychology, 2017)
Aim: Periodontal therapy is highly dependent on a patient's long-term adherence with regard to oral hygiene, diet, and regular check-ups at the dentist. Motivational Interviewing (MI) is a client-centered, directive method for encouraging a patients' behavioral health change. The aim of this systematic review was to reveal the effects of MI as an adjunct to periodontal therapy. Methods: Three databases (PubMed, Cochrane Library, and Web of Science) were reviewed for randomized controlled clinical trials. Articles were included when using MI as an adjunct to periodontal therapy and presenting clinical periodontal and oral hygiene related parameters. Two authors independently coded the relevant articles. Results: The search yielded 496 articles. After analysis and exclusion, a total of five papers could be included. The quality of the articles ranged between 72–88%. The two independent raters showed a high inter-rater reliability (Cohens-Kappa = 0.89). In two studies MI showed a significant positive effect on bleeding on probing and plaque values. One study showed improvement of self-efficacy in interdental cleaning. Two studies showed no influence of MI on periodontal parameters of the patients. Conclusion: The use of MI as an adjunct to periodontal therapy might have a positive influence on clinical periodontal parameters (plaque values, gingival, and periodontal inflammation) and psychological factors related to oral hygiene (self-efficacy). Due to the low body of evidence further studies are needed. Future studies should include fidelity measures of the applied MI, a high number of counselors, several MI sessions, and long-term study follow-up to show potential effects.